EPIDEMIOLOGICAL AND SOCIAL ASPECTS OF CASES OF AIDS WHO DIED IN THE STATE OF RIO GRANDE DO NORTE (Fiep Bulletin - online, 2015)
The study aimed to analyze the epidemiological and social aspects of AIDS cases that died in the state of Rio Grande do Norte, in the period 2000 to 2013. This is a descriptive, retrospective study using Database Information System on Mortality (ISM), Brazilian Institute of Geography and Statistics (IBGE). The information has been compiled for Excel and SPSS 20.0 software. The results showed that 66.4% of deaths were males in adulthood, and the largest number of cases is located in the Eastern Region which includes the state capital and the metropolitan area, and also in the western region, which is situated second largest city in the state, but no significant differences were found between the variables. Given the results, it was concluded that cases of AIDS have evolved deaths are concentrated in large centers (Natal  and Mossoró), with a predominance of adult males.
Keywords: Acquired Immunodeficiency Syndrome; Morbidity and mortality.